2017
DOI: 10.1002/phar.2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioavailability of Single‐Dose Extended‐Release Venlafaxine Capsules in Obese Patients Before and After Gastric Bypass Surgery

Abstract: This study suggests that RYGB does not significantly alter the amount of venlafaxine or its active metabolite, ODV, absorbed from a venlafaxine ER capsule or the time over which it is absorbed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Venlafaxine, a serotonin‐norepinephrine reuptake inhibitor (SNRI), is also predominantly metabolized by CYP2D6 into its major active metabolite, O ‐desmethylvenlafaxine . The effect of RYGBP on venlafaxine exposure was investigated in a prospective, single‐dose study presurgery and 3 to 4 months after surgery . There were no significant differences in venlafaxine exposure, C max and T max , neither prior to or after RYGBP, substantiating the metoprolol findings above of an unaltered CYP2D6 activity.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Venlafaxine, a serotonin‐norepinephrine reuptake inhibitor (SNRI), is also predominantly metabolized by CYP2D6 into its major active metabolite, O ‐desmethylvenlafaxine . The effect of RYGBP on venlafaxine exposure was investigated in a prospective, single‐dose study presurgery and 3 to 4 months after surgery . There were no significant differences in venlafaxine exposure, C max and T max , neither prior to or after RYGBP, substantiating the metoprolol findings above of an unaltered CYP2D6 activity.…”
Section: Resultsmentioning
confidence: 64%
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
“…In studies of caffeine, tolbutamide, omeprazole, and venlafaxine, pharmacokinetic parameters were not changed after RYGB, apart from a significantly shorter time to peak serum concentration ( T max ) . Increased morphine exposure after RYGB has been reported, however …”
Section: Introductionmentioning
confidence: 98%
“…Of the total 21 studies, some conducted more than one procedure: 19 studies investigated RYGB, five investigated SG, two investigated BPD‐DS, and one study investigated mini‐GB . The number of participants in these studies ranged from five patients in a single study to a maximum of 34 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the included articles, 11 studies reported a statistically significant change in pharmacokinetics before and after a bariatric procedure, measured as a change in either C max , T max , or AUC with statistical significance determined with a P value lower than .05. In six studies, the results were either reported as nonsignificant or the P values presented were above the threshold for statistical significance ( P < .05). In a further five studies, there was a reported pharmacokinetic change but neither P value nor statistical significance for a change in the reported parameters was reported.…”
Section: Resultsmentioning
confidence: 99%